Use of a PbO2 electrode of a lead-acid battery for the electrochemical degradation of methylene blue. Issue 9 (13th June 2017) - Saaidia, Samia; Delimi, Rachid; Benredjem, Zahia; Mehellou, Ahmed; Djemel, Abdelhak; Barbari, Karima
ABSTRACT: In this work, the electrochemical degradation efficiency of synthetic azo dye, methylene blue, at positive electrode PbO2 of lead-acid battery was investigated. The structure and morphology of the electrode was investigated by X-ray diffraction, scanning electron microscopy, and energy dispersive X-ray spectrometry. The influence of several operating parameters on electro-oxidation of 100 mL of methylene blue solution 100 mg/L was studied. Results indicated that lead-acid battery electrode is effective for removing color and chemical oxygen demand (COD). It is found that current density, the stirring speed, and the supporting electrolyte concentration have a positive effect on decolorization and mineralization, and no significant effect of the distance between the electrodes on methylene blue degradation and COD removal was observed. By contrast, the percentage of color and COD removal decreases with increasing of pH. Kinetic analysis of the results revealed that the COD removal follows a pseudo-first-order kinetics.